Public Attitudes Towards National Issues in Interactive Television Programs - Talib, Ahmed Sami; Al-Tamimi, Montaha Hadi (ALBAHITH ALALAMI, 2023)
This research aims to investigate the extent to which the Iraqi audience relies on interactive television programs as a source of information regarding national issues and their resulting impacts. It seeks to identify the types and nature of attitudes developed among the public towards national issues through these programs and determine the prominent topics and issues highlighted to the audience. The researcher employed a field survey as the primary research method, employing a questionnaire for data collection along with scientific observation and the Likert three-point scale to measure attitudes. The study was guided by the media dependency theory. A sample of 520 questionnaires was distributed to residents in Baghdad province using a multi-stage cluster and purposive sampling approach. The study yielded several notable findings, including:1. The sample participants exhibited a high level of interest in following national issues on satellite channels, with %98.4 indicating their engagement.2. Cognitive motives and goals, such as understanding and guidance, ranked as the most significant motivations for relying on satellite channels as a source of information on national issues.